Urinary Tract Infection by Nalidixic Acid Resistant Salmonella enterica Serotype Typhi - Bhatta, Sabita; Chaudhary, Raina; Hamal, Bhairab Kumar (Medical Journal of Shree Birendra Hospital, 2016)
Salmonella species are a rare cause of urinary tract infection in humans.Recovery of S. Typhi from urine is rare and can occur following a recent episode of typhoid fever or in a chronic carrier states involving the urinary system. It has been associated with a higher incidence of structural abnormalities of urinary tract. We report a case of a 50 year old female with urinary tract infection caused by Nalidixic acid resistant Salmonella typhi in association with nephrolithiasis.